2018
DOI: 10.1039/c8ta05794j
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance factors of hybrid organic–inorganic perovskites: recent improvements and current state of research

Abstract: We provide an update on the current state of the tolerance factor concept for hybrid organic–inorganic perovskites, reviewing the different improvements that have been made over the past few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 100 publications
2
49
0
Order By: Relevance
“…TF > 1 implies that A cation is too large or B cation too small, while TF < 1 implies A cation is too small or B cation too large. This concept is generalized to hybrid perovskites containing organic cations by Kieslich and Becker et al [37][38][39] It is found that the TF value of most hybrid perovskites lies in the range from 0.8 to 1. Hybrid perovskite structures with TF > 1 or TF < 0.8 are rarely observed.…”
Section: Resultsmentioning
confidence: 99%
“…TF > 1 implies that A cation is too large or B cation too small, while TF < 1 implies A cation is too small or B cation too large. This concept is generalized to hybrid perovskites containing organic cations by Kieslich and Becker et al [37][38][39] It is found that the TF value of most hybrid perovskites lies in the range from 0.8 to 1. Hybrid perovskite structures with TF > 1 or TF < 0.8 are rarely observed.…”
Section: Resultsmentioning
confidence: 99%
“…Deviations from the ideal perovskite cubic structure can occur, depending on the ratio of the ionic radii of both cations, expressed through the so‐called Goldschmidt tolerance factor t t=(rA+rO)2false(rnormalB+rnormalOfalse)with r A , r B, and r O the radii of the A, B cations, and normalO2 anions, respectively. Materials would crystalize in the cubic perovskites once t ≈1; for t < 1, we may expect the orthorhombic or even a non‐provskite structure, whereas for t > 1 one could expect the tetragonal or hexagonal structures .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Whilst the general structure-motif and building-principle of HOIPs and all-inorganic perovskites is similar, i.e. the Goldschmidt's Tolerance Factor concept is applicable to both families with only a few exceptions, 6,7 the possibility to introduce molecular ions offers additional opportunities such as weak molecular interactions that can be used for materials design. 8,9 For instance, it was shown that hydrogen bonding interactions between the A-cation and the negatively charged ReO3-type framework in HOIPs such as [CH3NH3]PbI3 or [NH3NH2]Zn(HCOO)3 play an important role in the order-disorder phase transitions as a function of temperature.…”
mentioning
confidence: 99%